Noonan syndrome with giant cell lesions - S. M. G. LEE, & J. C. COOPER (Paediatric Dentistry, 2005)
Noonan syndrome was first described in 1963 by Noonan and Ehmke1 [1], although the condition was first reported by Kobylinski in 1883 [2].